Comparison of CYP2C9 Activity in Ethiopian and Non-Ethiopian Jews Using Phenytoin as a Probe - Abu Ghosh, Zahi; Alamia, Shoshana; Shaul, Chanan; Caraco, Yoseph (Frontiers in Pharmacology, 2020)
The pharmacokinetics of CYP2C9 substrates is characterized by substantial interethnic variability. The objective of the study was to compare CYP2C9 activity by using Phenytoin Metabolic Ratio (PMR) between Ethiopian and non-Ethiopian Jews. PMR was derived from the ratio of p-HPPH in 24-hours urine collection to plasma phenytoin, 12 hours (PMR24/12) or 24 hours (PMR24/24) after the administration of 300 mg phenytoin. Analysis of CYP2C9*2, *3, *5, *6, *8 and *11 was carried by direct sequencing. PMR was significantly correlated with CYP2C9 genotype in both groups (p< 0.002). Mean PMR values were similar among Ethiopians and non-Ethiopians despite the fact that the fraction of non-carriers of CYP2C9 variant alleles was significantly different (85% vs. 53%, respectively, p< 0.001). However, among non-carriers of CYP2C9*2, *3, *5, *6, *8 and *11 variant alleles, PMR24/12 and PMR24/24 values were 30% and 34% greater respectively in the non-Ethiopians group (p< 0.001). In conclusion – CYP2C9 activity as measured by PMR is similar in Ethiopian and non-Ethiopian Jews. However, among non-carriers of CYP2C9 variant alleles accounting for 85% of Ethiopian Jews, CYP2C9 activity is decreased by approximately one third as compared with non-Ethiopian Jews. Unique genetic CYP2C9 polymorphisms occurring only in Ethiopians may account for this difference.